The survival benefit of different lymph node yields in radical prostatectomy for pN1M0 prostate cancer patients: Implications from a population-based study - Hu, Jieping; Yu, Yue; Liu, Wei; Zhong, Jialei; Zhou, Xiaochen; Xi, Haibo (Frontiers in Oncology, 2022)
Background and Objectives: The extent and survival benefits of lymph node dissection (LND) in radical prostatectomy (RP) for pN1M0 prostate cancer (PCa) patients remained unclear and was controversial. This study was to determine the survival benefit of different lymph node yields in RP for pN1M0 PCa patients. Methods: pN1M0 PCa patients who received RP and LND were identified in Surveillance Epidemiology and End Results (SEER) (2010–2015). Patients were divided into two groups in SEER based on the removal of 1 to 3 regional lymph nodes (LND1 group) or 4 or more regional lymph nodes (LND4 group). Kaplan-Meier methods were used to calculate cancer-specific survival (CSS) and overall survival (OS). Results: In total, 2200 patients were identified and 264 patients received LND1, 1936 patients received LND4. CSS was no significant difference between the LND4 and LND1 group(101mon VS 98mon, p=0.064), OS was higher in LND4 patients compared with LND1 patients (97mon VS 93mon, p=0.024), for patients with Gleason score=9 or 10 and T3b or T4, 5-year OS was higher in patients undergoing LND4 (80.9%; 95% CI, 79.0-82.8) compared with LND1 (67.5%; 95% CI, 60.8-74.2)(p=0.009). Conclusion: More lymph node yield provided better survival for patients with Gleason score=9 or 10 and T3b or T4, but not for other pN1M0 prostate cancer patients. The extent of lymph node dissection would be determined after a comprehensive evaluation including Gleason score, tumor stage, and general condition of the patient.